Maqashid Sharia Progressive: Anatomical and Transformational of Halal Institutions in UIN KHAS Jember - Wicaksono, Syafril; Al-Asy'ari, M. Khoirul Hadi; El-Adibah, Elisa Dourothun Nafis; Iffahasanah, Iffahasanah (El-Mashlahah, 2023)
The research discussed the Audit Institutions Halal (LPH) at the State Islamic University Kiai Haji Achmad Siddiq Jember (UIN KHAS Jember) regarding the halal industry movement. However, the existence of a halal institution for the halal certification movement is still not effective in implementing local social and customary communities since the LPH, in substance, mostly does not work properly. Meanwhile, the university only acts as a tool. The research aimed to analyze the anatomical and transformational importance of halal institutions at UIN KHAS Jember which is studied using maqashid sharia progressive. It used an empirical legal research method with a descriptive qualitative data approach. The research shows that the existence of LPH, which is affiliated with universities, especially UIN KHAS Jember, provides space for good dissemination of information in the community, supported by academics in halal genealogy in Indonesia. LPH contributes positively to the institutional dimension and outreach to the community. However, the dimensions of the law of Halal Product Certification still provide room for polemics, for example, halal localities in indigenous communities in Indonesia, which should receive legal recognition. The aim is to avoid the statement of Jasser Auda that worried things about maqashid sharia, namely a feature about the absence of a halal monopoly, which is only in the hands of the government but also exists within existing customary institutions.